Changes in the Neighborhood Food Store Environment and Children's Body Mass Index at Peripuberty in the United States - Chen, Hsin-Jen; Wang, Youfa (Journal of adolescent health, 2016)
Little is known about the relationship between changes in food store environment and children's obesity risk in the United States. This study examines children's weight status associated with the changes in the quantity of food stores in their neighborhoods. A nationally representative cohort of schoolchildren in the United States was followed from fifth grade in 2004 to eighth grade in 2007 (n = 7,090). In 2004 and 2007, children's body mass index (BMI) was directly measured in schools. ZIP Code Business Patterns data from the Census Bureau in 2004 and 2007 characterized the numbers of food stores in every ZIP code area by type of store: supermarkets, limited-service restaurants, small-size grocery, and convenience stores. Baseline and change in the numbers of stores were the major exposures of interest. Girls living in neighborhoods with three or more supermarkets had a lower BMI 3 years later (by −.62 kg/m2; 95% confidence interval = −1.05 to −.18) than did those living in neighborhoods without any supermarkets. Girls living in neighborhoods with many limited-service restaurants had a greater BMI 3 years later (by 1.02 kg/m2; 95% confidence interval = .36–1.68) than did those living in neighborhoods with less than or equal to one limited-service restaurant. Exposure to a decreased quantity of small-size grocery stores in neighborhoods was associated with girls' lower BMI by eighth grade. The longitudinal association between neighborhood food environment and children's BMI differed by gender. For girls, supermarkets in neighborhoods seemed protective against obesity, whereas small-size grocery stores and limited-service restaurants in neighborhoods increased obesity risk. There was no significant longitudinal finding for boys.